2005
DOI: 10.1038/ng1618
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic tandem repeats generate functional variability

Abstract: Tandemly repeated DNA sequences are highly dynamic components of genomes. Most repeats are in intergenic regions, but some are in coding sequences or pseudogenes. In humans, expansion of intragenic triplet repeats is associated with various diseases, including Huntington chorea and fragile X syndrome. The persistence of intragenic repeats in genomes suggests that there is a compensating benefit. Here we show that in the genome of Saccharomyces cerevisiae, most genes containing intragenic repeats encode cell-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
629
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(655 citation statements)
references
References 29 publications
18
629
2
6
Order By: Relevance
“…Evidence of tandem gene duplication and high levels of polymorphism suggests that spidroins are naturally selected to maintain diversity. The presence of long arrays of tandem repeats in spidroins, reminiscent of those that facilitate rapid variation on microbial cell surfaces 61 and morphological plasticity in mammals 62 , also suggests a gene family undergoing continuous evolution. In particular, N. clavipes spidroin gene phylogenies ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of tandem gene duplication and high levels of polymorphism suggests that spidroins are naturally selected to maintain diversity. The presence of long arrays of tandem repeats in spidroins, reminiscent of those that facilitate rapid variation on microbial cell surfaces 61 and morphological plasticity in mammals 62 , also suggests a gene family undergoing continuous evolution. In particular, N. clavipes spidroin gene phylogenies ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes are believed to be facilitated by the nature of the genes responsible for flocculation in yeast strains, which contain many tandem repeats 52 and are consequently highly susceptible to mutation without causing a loss in viability 42,51 . Analysis of flocculation using the Helms assay revealed that BridgePort lager yeast was moderately flocculent (41.45 ± 8.67) when grown in synthetic media (YPD), while the ale strain was more strongly flocculent (86.0 ± 6.4).…”
Section: Effect Of Extended Serial Repitching On Yeast Flocculation Cmentioning
confidence: 99%
“…They enable rearrangements both between and within flocculin genes. Several studies have shown that the longer the Flo protein (carrying more repeats) the stronger is the flocculation ability it confers 30,105,111 . Accordingly, FLO1 was observed to be the longest FLO gene, with the most repeats and to confer the strongest flocculation phenotype 104 .…”
Section: The Flo Family Genes Are Unstablementioning
confidence: 99%
“…FLO genes are very long (up to 4.6 kbp) because of tandem repeated DNA sequences of about 100 nucleotides that are repeated 10-20 times in each gene 104,105 . Tandem repeated DNA sequences in the FLO genes are highly dynamic components of the genome, i.e.…”
Section: The Flo Family Genes Are Unstablementioning
confidence: 99%